2021
DOI: 10.3892/ol.2021.12546
|View full text |Cite
|
Sign up to set email alerts
|

In vivo, ex vivo and in vitro dasatinib activity in chronic lymphocytic leukemia

Abstract: Dasatinib inhibits the breakpoint cluster region-Abelson murine leukemia 1 ( BCR-ABL1 ) gene along with other kinases known to be overexpressed and abnormally active in patients with chronic lymphocytic leukemia (CLL). The current study used primary leukemic cells obtained from 53 patients with CLL that were treated with dasatinib. A 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) assay and Annexin V staining was performed to assess the cytotoxic effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Imatinib inhibits c-ABL kinase activity resulting in a decrease in Rad51 phosphorylation, leading to a repair of chlorambucil-induced DNA damage ( 16 ). CLL patients are more likely to have increased c-ABL in humans ( 17 , 18 ). Moreover, one human case study reported that imatinib was used effectively for the treatment of CLL and chronic myelogenous leukemia, showing decrease of peripheral blood CLL cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib inhibits c-ABL kinase activity resulting in a decrease in Rad51 phosphorylation, leading to a repair of chlorambucil-induced DNA damage ( 16 ). CLL patients are more likely to have increased c-ABL in humans ( 17 , 18 ). Moreover, one human case study reported that imatinib was used effectively for the treatment of CLL and chronic myelogenous leukemia, showing decrease of peripheral blood CLL cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%